Contributions on high impedance fault classification in microgrids using harmonic synchrophasors - Cieslak, Dionatan Augusto Guimarães (2024)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Elétrica, Florianópolis, 2024.